Hydrothermal crystal growth, structures and thermal properties of Co(II)-4,4′-bipyridine-based coordination polymeric materials - Sanchai Luachan (2018)
Hydrothermal synthetic parameters were studied and optimized for the preparation of new coordination polymeric materials based on Co(II) and 4,4′-bipy. A new polymeric compound, [Co2(H2O)2(OH)2(4,4′-bipy)8](NO3)2·2(4,4′-bipy) 10(H2O) (1), was prepared and structurally characterized by single crystal experiment. The framework of (1) is made up of two different one-dimensional substructures, i.e., the neutral chain A and positively charged chain B, both of which share the same nodes and node linkers. This is rarely found, especially from a one-pot crystal growth technique. Two other crystals were also identified, i.e., [Co(SO4)(H2O)3(4,4′-bipy)]·2(H2O), and K2Co(H2O)6(SO4)2. The optimization of synthetic parameters apparently favors the formation of different polymeric structures, and this can be experimentally fine tuned. The influences of these parameters on phase formation, purity and crystal growth are discussed. The complicated thermogravimetric property of the new compound is also reported. © 2007 Springer Science+Business Media, LLC.